PERBEDAAN E-WOM KUALITAS INFORMASI, KREDIBILITAS INFORMASI, KEGUNAAN INFORMASI, DAN ADOPSI INFORMASI ANTARA MEDIA SOSIAL DAN SITUS BELANJA PADA NIAT PEMBELIAN PRODUK FASHION - Farid Farid; Irma Yanti (Departemen Manajemen, Universitas Syiah Kuala, 2018)
This research aims to know the difference e-WOM quality of information, the credibility of the information, usefulness of information and the adoption of information between social media and shopping website on the purchase intention of the products fashion in the city of Banda Aceh. The sample used in this research is as much as 150 respondents who use social media platforms and shopping website on the purchase intention of the products fashion. Sampling techniques using purposive sampling. A method the data used to test the difference is test different paired sample t-test. The results of this research showed that there was a difference in the quality of the information, the credibility of the information, usefulness of information and the adoption of information between social media and shopping website on the purchase intention of the products fashion in the city of Banda Aceh. This research also offers insights for social media users and shopping website in the search for information about the fashion products to get the best quality of information and make the customers satisfied with the decisions that have been selected. Keywords: WOM, e-WOM, Information Quality, Information Credibility, Information Usefulness, Information Adoption, Purchase Intentions, Social Media, Shopping Website